A Research Review of the Good Character of the Prophet Muhammad (peace be upon him) in the Light of his Biography - Tasaur Saba D/O Muhammad Yaqoob Kazmi; Associate Professor Dr. Naseem Akhtar (Journal of Religion and Society, 2025)
The example of the Prophet Muhammad (PBUH) was a very practical remedy of the noblest character in life. He was just, compassionate, and gentle in all the spheres of Life. And he stressed the fact that one should respect the rights of each person, parents, spouses, children, and neighbors. He was good to orphans, poor people, and even animals. The women have been given honor and protection in his teachings. He was fair and just to the Muslims and non-Muslims. He preached that human beings are equal before Allah (SWT). His actions were characterized by tolerance, meekness, and strong empathy. He was persistent even during hard situations. He even had mercy on his people and blessed them with enlightenment. His precepts paved the way for a brand new society of justice and mercy. He enhanced love, forgiveness, and respect for one another in society. The example provided by him opposed the harmful traditions and the individual ego. This is what he taught mankind that we owe our obligations not only to Allah (SWT) but to ourselves as well. This short summary identifies the ethical behavior of the Prophet (PBUH) employers who based his behavior on the notion of rights and duties. His personality is an eternal guide to this inequality and unfair world nowadays. His superior countries also taught us that we have to treat people with good character, we have to treat men as well as women, poor people, neighborhoods and Muslims, and non-Muslims. When doing so, follow his example, and we can create a better place that is kinder, equal, and morally upright. Keywords: Prophet Muhammad (PBUH), Non-Muslims, Fairness and justice